Using Brain-Based Learning to Promote Students’ Concept Mastery in Learning Electric Circuit - Aulianuriy Sani; Diana Rochintaniawati; Nanang Winarno (Journal of Science Learning, 2019)
Teaching approaches in some school are still concentrating on memorizing. Teachers have to make the learning is meaningful for the students. One of the alternative tool is by using Brain-Based Learning. The purpose of this study is to investigate the effect of Brain-Based Learning on students’ concept mastery in learning electric circuit for 8th-grade students. The method used in this research was experimental research. The research design that used is pretest and posttest design. The sample was taken by cluster random sampling technique. Participants were 49 students at one of International Secondary School in Bandung, West Java, Indonesia. Experiment group learn with Brain-Based Learning (N=26) while control group learn with lectured based learning (N=23). The results of students’ concept mastery that learned using Brain-Based Learning is better than students’ concept mastery that learned using lectured-based learning. The improvement of students’ concept mastery can be noticed by independent t-test with significant 0.003. Based on the analysis of students’ concept mastery results, the N-Gain score in experiment group is 0.43 which categorized as medium improvement while in control group is 0.25 which categorized as low improvement. Based on this results showed that Brain-Based Learning can be an alternative tool to improve students’ concept mastery significantly.